Bringing Porous Organic and Carbon‐Based Materials toward Thin‐Film Applications - Wuttke, Stefan; Medina, Dana D.; Rotter, Julian M.; Begum, Salma; Stassin, Timothée; Ameloot, Rob; Oschatz, Martin; Tsotsalas, Manuel (Advanced functional materials, 2018)
Porous materials have attracted tremendous scientific and industrial interest due to their broad commercial applicability. However, some applications require that these materials are deposited on surfaces to create thin films. Here, the recent progress of new porous thin‐film material classes is described: porous organic molecular materials, porous organic polymers, covalent organic frameworks, and nanoporous carbon. In each case, the state of the art and current barriers in their thin‐film fabrication, as well as intrinsic material advantages that are suited for different applications are presented. By highlighting the unique structural characteristics and properties of these materials, it is hoped that increased research development and industrial interest will be fostered, which will lead to new methods of thin‐film synthesis and consequently to new applications. Recent advances, challenges, and future perspectives on bringing novel microporous materials toward thin‐film application are reviewed. The state of the art and current barriers in the thin‐film fabrication of porous organic molecular materials, porous organic polymers, covalent organic frameworks, and nanoporous carbon are described, and, in each case, intrinsic material advantages suited for different applications are highlighted.